Analisis Fungsi Produksi Usahatani Kelapa dan Respon Petani Kelapa di Kabupaten Indragiri Hilir - SABARMAN DAMANIK; DEDI SOLEH EFFENDI (Buletin Palma, 2009)
Production Function Analysis of Coconut Farming System and Coconut Farmers Respose in Indragiri Hilir DistrictThe research is conducted in sub-district Tempuling, Indragiri Hilir, Riau Province for two years February 2004 - February 2006). Technical aspect, economy and social data are taken from 120 coconut base farming community based organization program participant. Farming system analysis is conducted using sutvey method by preparing question-list for the farmers that are participating in Community Base Orga-nization (CBO). The objectives of this research and the interview to 20 farmer respondent are done using random sampling from 120 farmer that are participating in CBO. The objectives of this research are to analyse the functional form ofcoconut farming production and find out farmers response on coconut farming in community base organi-zation. Methodology of this research are production function translog and response analysis. Parameters that being observed are the amount of production, seeds, vertilizer and labor. Typically for response analysis the parameters being observed are income, wide farm, education and participation in CBO group. The result of production function analysis with three input factors (seed, vertilizer and labor) showed that farmer position as aproducer is at increasing return to scale condition which mean that the use of seeds, vertilizers and labors still can be increase to reach maximum profitability. By that result it is still possible to add more input factor. Average elasticity coefficient number for seed is 0.5323, vertilizer input 0.0148 and labor input 4.377. The best elasticity coefficient number is from labor input which indicate for every labor addition will increased production level equal to 0.83 percent. For farmer level of respon to CBO base farming program are affected by level of income and available labors. The higher income and labors level will make the farmer more active in participating CBO based= coconut farming program which will automatically increase the coconut crop production and quality.